Comparison of Central Macular Thickness Measured by Three OCT Models and Study of Interoperator Variability - Zaïnab Bentaleb-Machkour; Eléonore Jouffroy; Muriel Rabilloud; Jean-Daniel Grange; Laurent Kodjikian (The Scientific World Journal)
Purpose. To compare central macular thickness (CMT) measurement on healthy patient using 3 different OCT devices by two operators. Methods. Prospective, monocentricstudy. Right eye’s central macular thickness (CMT) of 30 healthy patients has been measured three times using a time-domain (TD) OCT (Stratus OCT, Carl Zeiss Meditec, Dublin, Ca) and two spectral domain (SD) OCTs (Cirrus HD-OCT, Carl ZeissMeditec, Dublin, Ca) and 3D-OCT 1000 (Topcon, Tokyo, Japan) by two operators. Six measurements were taken randomly for each patient the same day. Results. No significant difference between measurements obtained by the two operators has been observed, whatever the studied OCT. P value was 0.164, 0.193, and 0.147 for Stratus OCT, Cirrus HD-OCT and 3D-OCT, respectively. Mean CMT significantly differed from instrument to instrument (P<0.001) and was, respectively, 197 μm, 254 μm, and 236 μm using Stratus OCT, Cirrus HD-OCT, and 3D-OCT 1000. Using Cirrus OCT and 3D-OCT 1000, CMT was, respectively, 57 μm and 39 μm thicker than using Stratus OCT (P<0.05). Conclusions. Whatever the OCT device, on healthy patients CMT was not operator dependent. CMT measurements obtained by SD-OCTs are greater than those obtained by TD-OCT. These data imply that the different OCT devices cannot be used interchangeably in clinical monitoring.